Coexistence of chronic lymphocytic leukemia and multiple myeloma, do the roots of these entities originate from the same place? - Merdin, Alparslan (Clin Case Rep, 2017)
Multiple myeloma is a plasma cell disease, whereas CLL (Chronic Lymphocytic Leukemia) affects mature B‐cell lymphocytes. Even though the coexistence of those two conditions is extremely rare, as both cell types differentiate from the same multipotent stem cells, the clinician should evaluate patients carefully not to misdiagnose such a concomitancy.